Sequential Accumulation of 'Driver' Pathway Mutations Induces the Upregulation of Hydrogen-Sulfide-Producing Enzymes in Human Colonic Epithelial Cell Organoids - Kelly Ascenção; Nahzli Dilek; Karim Zuhra; Katalin Módis; Toshiro Sato; Csaba Szabo (MDPI AG, 2022)
Recently, a CRISPR-Cas9 genome-editing system was developed with introduced sequential 'driver' mutations in the WNT, MAPK, TGF-β, TP53 and PI3K pathways into organoids derived from normal human intestinal epithelial cells. Prior studies have demonstrated that isogenic organoids harboring mutations in the tumor suppressor genes APC, SMAD4 and TP53, as well as the oncogene KRAS, assumed more proliferative and invasive properties in vitro and in vivo. A separate body of studies implicates the role of various hydrogen sulfide (H2S)-producing enzymes in the pathogenesis of colon cancer. The current study was designed to determine if the sequential mutations in the above pathway affect the expression of various H2S producing enzymes. Western blotting was used to detect the expression of the H2S-producing enzymes cystathionine β-synthase (CBS), cystathionine γ-lyase (CSE) and 3-mercaptopyruvate sulfurtransferase (3-MST), as well as several key enzymes involved in H2S degradation such as thiosulfate sulfurtransferase/rhodanese (TST), ethylmalonic encephalopathy 1 protein/persulfide dioxygenase (ETHE1) and sulfide-quinone oxidoreductase (SQR). H2S levels were detected by live-cell imaging using a fluorescent H2S probe. Bioenergetic parameters were assessed by Extracellular Flux Analysis; markers of epithelial-mesenchymal transition (EMT) were assessed by Western blotting. The results show that the consecutive mutations produced gradual upregulations in CBS expression-in particular in its truncated (45 kDa) form-as well as in CSE and 3-MST expression. In more advanced organoids, when the upregulation of H2S-producing enzymes coincided with the downregulation of the H2S-degrading enzyme SQR, increased H2S generation was also detected. This effect coincided with the upregulation of cellular bioenergetics (mitochondrial respiration and/or glycolysis) and an upregulation of the Wnt/β-catenin pathway, a key effector of EMT. Thus sequential mutations in colon epithelial cells according to the Vogelstein sequence are associated with a gradual upregulation of multiple H2S generating pathways, which, in turn, translates into functional changes in cellular bioenergetics and dedifferentiation, producing more aggressive and more invasive colon cancer phenotypes.